In vitro assessment of phytochemicals, antioxidant and DNA protective potential of wild edible fruit of Elaeagnus latifolia Linn. (11th July 2014) - Panja, Sourav; Chaudhuri, Dipankar; Baban Ghate, Nikhil; Le Minh, Ha; Mandal, Nripendranath
Abstract : Introduction . Elaeagnus latifolia Linn. is a type of wild edible fruit found in northeast India, Thailand and also in Vietnam. Although the fruit is reported to be a source of vitamins, minerals, essential fatty acids and other bioactive compounds, only a few studies have been concerned with the antioxidant activity of this plant.Materials and methods . Our study revealed in vitro antioxidant and free radical scavenging activity of 70% methanolic extract of Elaeagnus latifolia Linn. (ELME). Various tests including identification and quantification of phytochemicals, total antioxidant activity, hydroxyl radical, superoxide radical, singlet oxygen, hypochlorous acid scavenging, reducing power and DNA protection assays were performed.Results and discussion . Among the tests, ELME scavenged superoxide radical [IC50 = (150.78 ± 4.2) μg×mL–1], hydroxyl radical [IC50 = (238.09 ± 11.63) μg×mL–1] and protected pUC18 DNA [P50 = (695.91 ± 15.84) μg×mL–1]; P50 signifies the concentration for 50% protection . The fruit is found to be a source of minute amounts of carbohydrates, ascorbic acid, tannins, phenolics and flavonoids. HPLC data showed that purpurin, tannic acid, quercetin, catechin, reserpine and rutin are present in ELME.Conclusion . Our results provide evidence that 70% methanol extract of E. latifolia Linn. acts as a promising antioxidant as well as DNA protector, which is partly due to the phenolic and flavonoid compounds present in it.